2019
DOI: 10.1101/648501
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

TGFβ drives mitochondrial dysfunction in peripheral blood NK cells during metastatic breast cancer

Abstract: Natural Killer (NK) cells provide important protection from cancer and are a key requirement for particular immunotherapies. In activated NK cells, a metabolic response towards increased glycolysis and oxidative phosphorylation is crucial for NK cell effector functions. However, there is accumulating evidence that NK cells become dysfunctional during chronic inflammatory diseases, such as human breast cancer. This dysfunction is apparent in peripheral blood NK cells and can impact on normal NK cell immune resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…Recent work from our lab showed that peripheral blood NK cells from patients with metastatic breast cancer have severely reduced levels of metabolism and impaired mTORC1 activity (54). Neutralization of TGFβ ex vivo restored levels of oxphos, mTORC1 activity, nutrient receptor expression and importantly, IFNγ production.…”
Section: Tgfβ and Nk Cell Metabolismmentioning
confidence: 92%
See 2 more Smart Citations
“…Recent work from our lab showed that peripheral blood NK cells from patients with metastatic breast cancer have severely reduced levels of metabolism and impaired mTORC1 activity (54). Neutralization of TGFβ ex vivo restored levels of oxphos, mTORC1 activity, nutrient receptor expression and importantly, IFNγ production.…”
Section: Tgfβ and Nk Cell Metabolismmentioning
confidence: 92%
“…Excessive ROS may also result in aberrant cell signaling through oxidative modification of redox-sensitive signaling proteins e.g., MAPK, HIF or NFkB (70). Recent studies showed that excessive ROS production is associated with NK cell metabolic dysfunction in metastatic breast cancer patients and in childhood obesity (54,71). Interestingly, there is significant evidence demonstrating a connection between TGFβ and ROS production, with TGFβ treatment stimulating ROS production in many different studies.…”
Section: Tgfβ and Rosmentioning
confidence: 99%
See 1 more Smart Citation
“…The tumor microenvironment contains large amounts of immunosuppressive cytokines and other soluble factors that affect NK cell functionality, with one of the most prominent being TGF-β (25). In addition to inducing downregulation of surface NKG2D, resulting in decreased cytotoxicity (26), TGF-β has been shown to be able to alter cytotoxicity, cytokine production, metabolism, and mitochondrial function in NK cells (27)(28)(29). Recent studies proposed that TGF-β also converts NK cells into noncytotoxic group 1 innate lymphoid cells (ILCs), allowing for tumor growth and metastasis in mice (30,31).…”
Section: Adoptive Nk Cell Therapymentioning
confidence: 99%
“…mTOR activity is required for increased glycolysis and mitochondrial functions during NK cell activation. Pharmacological inhibition of mTOR by rapamycin reduces the upregulation of glycolysis in mouse NK cells stimulated by IL-2/IL-12, and leads to a decrease in mitochondrial mass and membrane potential in human NK cells stimulated by IL-2, resulting in impaired effector functions ( 36 , 55 ). Consistently, CD56 bright NK cells that exhibit stronger metabolic responses to IL-2 or IL-12/IL-15 stimulation, have higher mTOR activity compared with CD56 dim NK cells ( 40 ); however, excessive activation of mTOR can cause mitochondrial fragmentation, thereby damaging mitochondrial function ( 37 ).…”
Section: Basic Nk Cell Metabolismmentioning
confidence: 99%